Die Schwarze Theologie von Allan Boesak – mit besonderem Hinweis auf seine Anthropologie - J.H. (Amie) van Wyk (HTS Teologiese Studies/Theological Studies, 2003)
The Black Theology of Allan Boesak – with specific reference to his anthropology Allan Boesak is a well known theologian and political reformer in the South African context. In this article the author scrutinises the political theology of Boesak in general and his anthropology in particular. The last section of the article is devoted to an assessment of Boesak's contribution as developed within the broader context of the theology of liberation. The investigation clarifies the fact that, although Boesak represents a more moderate kind of liberation theology, serious questions could still be raised about some of his insights.